The image of the non-Jew in Judaism : the idea of Noahide law - Novak, David, 1941- (Littman library of Jewish civilization (Series), 2011)
This classic study is the first critical treatment, from a historical and philosophical perspective, of the traditional Jewish approach to relations between Jews and non-Jews.